PENDAMPINGAN PENERAPAN PROTOKOL KESEHATAN PENYELENGGARAAN KEGIATAN DI SEKOLAH PADA MASA KENORMALAN BARU PANDEMI COVID-19 - Rudi Saprudin Darwis; Sri Sulastri; Gofarana Wilar (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The Covid-19 pandemic has forced people to change their behavior patterns to suit the situation and conditions during the pandemic, which is called the new normal. One of the things that must change is the pattern of education that must be accompanied by adjustments to the behavior of teachers and students in the learning process. At the time the government implemented Limited Face-to-face Learning (PTMT) there were still many. For this reason, this study aims to support the government's efforts to maintain the sustainability of education by assisting the implementation of health protocols in elementary schools during the new normal period of the Covid-19 pandemic. The study was conducted at SDN Pelangi 1 Sukamukti Village, Majalaya District, Bandung Regency. The method used in mentoring the implementation of health protocols is an extension method accompanied by a simulation of the practice of implementing the 3M health protocol (wearing masks, keeping distance, washing hands) which is attended by half of the students from grades 1 to 6. The results of the mentoring show that the students who initially did not recognize the scope of 3M and how it was implemented correctly, by the end of the activity most of them had applied how to wear masks properly, wash their hands properly, and tend to avoid crowds.